EASY WAYS OF MAKING PARAGRAPHS IN ENGLISH - Xolboyev Xushbek Ashirbekovich; Nurmuxamedova Iroda Aynabekovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article pays great attention to the methods of teaching as well as learning how to make a relevant paragraph in the English language and written according to new technologies.All differences and advantages of new methods described widely and exactly in this article and the teacher tries to give samples from his experience, which are considered very important for both teachers and learners.